Anxiolysis for laceration repair in children: study protocol for an open-label multicenter adaptive trial (ALICE) - Naveen Poonai; Vinolia Arthur-Hayward; Samina Ali; Vikram Sabhaney; Quynh Doan; Evelyne Trottier; Jocelyn Gravel; Nam Anh Tran; Maala Bhatt; Mohamed Eltorki; Jennifer Thull-Freedman; Julie Leung; et al. (PLoS ONE, 2025)
Background Lacerations are the most common traumatic reason for children to visit an emergency department (ED), accounting for almost half of all procedures performed. Children experience considerable distress during laceration repair, despite routine application of local anesthetic. Pharmacologic anxiolysis may mitigate the negative practice of forcefully restraining a child, however, evidence for the most effective agent is lacking. We aim to determine the most effective anxiolytic agent for laceration repair in children. Methods This is a multicentre, phase III, three-arm, adaptive, randomized, open-label, trial. We will include children 2–12 years with a single laceration requiring suture repair in the ED. Participants will be randomized to receive intranasal dexmedetomidine (IND) 3 mcg/kg, intranasal midazolam (INM) 0.4 mg/kg, or inhaled 50% nitrous oxide (N2O). The primary outcome is the weighted mean anxiolysis score using the Observational Scale of Behavioral Distress – Revised (OSBD-R) from initial positioning to tying of the last suture. Secondary outcomes include need for additional anxiolytic, need for physical restraint, adverse events (AEs), and delayed maladaptive behaviors. The primary analysis will be conducted by intention-to-treat. Results will report posterior means, standard deviations (SDs), and 95% high density posterior credible intervals for Total Distress Score on the OSBD-R. We will rank interventions based on the probability that an intervention is superior (Pbest) and the Surface Area Under the Cumulative Ranking Curve (SUCRA) to indicate relative anxiolytic efficacy. The mean difference in Total Distress Score and secondary outcomes will be estimated using Bayesian models. Ethics and dissemination Ethics approval will be obtained from institutional review boards of the participating sites. Informed consent will be obtained from guardians of all participants in addition to assent from all participants. Study data will be submitted for publication. Trial registration Clinicaltrials.gov NCT05383495